Hipertensión arterial y factores asociados en pacientes de la Unidad Operativa de Conzacola en el periodo 2017 - Cabrera Vega, Erika Nathaly (2019)
Arterial Hypertension (HTA) is characterized by a tension higher than 140 mm Hg and diastolic higher than 90 mm Hg. The objective of this study was to: Identify the degree of hypertension according to gender and age groups, describe the factors associated with hypertension and relate the degree of hypertension with the factors associated with the Conzacola operating unit in the 2017 period. Being a study descriptive, prospective, quantitative approach and cross-section, sample of 84 patients with a diagnosis of arterial hypertension, a survey was applied, blood pressure was quantified, following the European guidelines for Hypertension 2013.% (n = 20) women and 12% ( n = 10) males have high normal pressure; 24% (n = 20) women and 10% (n = 8) men HTA Grade I. The factors associated with HBP 41% (n = 22) women, 27% (n = 8) men do not perform physical exercise, 61% (n = 33) women, 60% (n = 18) males, have a family history; 56% (n = 30) women, 33% (n = 10) men have BMI> 25, 50% (n = 15) and 40% (n = 12) consume alcohol and smoke. HTA grade I is related to predisposing factors (n = 20) women do not exercise, BMI> 25 (n = 17); Males with high normal pressure; They are related to alcohol consumption (n = 24), smoking (n = 25). Concluding that the largest population which has been determined that women have more risk factors in comparison with men. Key words: High blood pressure, Risk factors, High normal pressure, Hypertension Grade I